Pendampingan Pembuatan Tempat Wudhu Air Panas Dingin Dan Ramah Lingkungan di Masjid Nurul Muttaqin Barengkrajan Krian Sidoarjo - Andrian Firdaus Yusuf al Qordhowi; Mohammad Djaelani (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Mosques are not only religious spaces but also public facilities that require environmentally sustainable management, particularly in the provision of ablution facilities. However, many mosque ablution areas in Indonesia still experience problems related to water inefficiency, lack of user comfort, and limited implementation of environmentally friendly technology. This community service activity aimed to assist in the development of an eco-friendly hot and cold water ablution facility at Masjid Nurul Muttaqin in order to improve worship comfort, water efficiency, and environmental awareness among the congregation. The program employed the Participatory Action Research (PAR) approach, emphasizing active community participation in planning, implementation, monitoring, and evaluation stages. Data were collected through participatory observation, interviews, documentation, and questionnaires, and analyzed qualitatively and descriptively. The results demonstrated that the installation of the hot and cold water system significantly improved the comfort and satisfaction of worshippers, particularly elderly users, while the environmentally friendly water management system contributed to reducing water waste and strengthening collective awareness regarding sustainable resource use. Furthermore, the participatory approach fostered a strong sense of ownership among mosque members, which supported the sustainability of the program.